Carboxyl-terminal Truncations of ClC-Kb Abolish Channel Activation by Barttin Via Modified Common Gating and Trafficking - Stölting, Gabriel (J Biol Chem, 2015)
ClC-K chloride channels are crucial for auditory transduction and urine concentration. Mutations in CLCNKB, the gene encoding the renal chloride channel hClC-Kb, cause Bartter syndrome type III, a human genetic condition characterized by polyuria, hypokalemia, and alkalosis. In recent years, several Bartter syndrome-associated mutations have been described that result in truncations of the intracellular carboxyl terminus of hClC-Kb. We here used a combination of whole-cell patch clamp, confocal imaging, co-immunoprecipitation, and surface biotinylation to study the functional consequences of a frequent CLCNKB mutation that creates a premature stop codon at Trp-610. We found that W610X leaves the association of hClC-Kb and the accessory subunit barttin unaffected, but impairs its regulation by barttin. W610X attenuates hClC-Kb surface membrane insertion. Moreover, W610X results in hClC-Kb channel opening in the absence of barttin and prevents further barttin-mediated activation. To describe how the carboxyl terminus modifies the regulation by barttin we used V166E rClC-K1. V166E rClC-K1 is active without barttin and exhibits prominent, barttin-regulated voltage-dependent gating. Electrophysiological characterization of truncated V166E rClC-K1 demonstrated that the distal carboxyl terminus is necessary for slow cooperative gating. Since barttin modifies this particular gating process, channels lacking the distal carboxyl-terminal domain are no longer regulated by the accessory subunit. Our results demonstrate that the carboxyl terminus of hClC-Kb is not part of the binding site for barttin, but functionally modifies the interplay with barttin. The loss-of-activation of truncated hClC-Kb channels in heterologous expression systems fully explains the reduced basolateral chloride conductance in affected kidneys and the clinical symptoms of Bartter syndrome patients.